Changes in soft tissue facial profile of class II skeletal malocclusion patients with retrognathic mandible treated with twin block appliance - Lin, Ng Hui; Soemantri, Eky Setiawan Soeria; Gayatri, Gita (Padjadjaran Journal of Dentistry, 2019)
Introduction: The soft tissue aspect in orthodontics treatment has gained attention in the last few years. The soft tissue profile is said to reflect the underlying skeletal profile, which causes a convex profile in patients with class II skeletal malocclusion. This research was aimed to determine the changes in the soft tissue facial profile of class II skeletal malocclusion patients with retrognathic mandible after twin block treatment. Methods: The type of research used in this study was retrospective descriptive research with paired t-test. The population was children aged 10-13 years old with class II skeletal malocclusion that were treated with twin block appliance in the Faculty of Dentistry Universitas Padjadjaran, Indonesia. The results of soft tissue changes before and after twin block treatment were compared. Results: There was an insignificant increase in soft tissue profile angle and Holdaway’s soft tissue angle after twin block treatment (p > 0.05). Whereas, Holdaway’s H-angle was decreasing and Merrifield’s Z-angle was increasing after twin block treatment, with statistically significant difference (p < 0.05). Conclusion: There was a decrease of H-angle, indicates a reduction in facial convexity and improvement of the facial profile after twin block treatment, but no difference in soft tissue profile angle and Holdaway’s soft tissue angle after twin block treatment. Keywords: Facial soft tissue profile, class II skeletal malocclusion, retrognathic mandible, twin block appliance